Formation of surface deformed layer of AZ31 magnesium alloy subjected to conventional mechanical grinding - Juliawati, Alias; Nasrul Azuan, Alang (Springer US, 2025)
In this study, the surface of an AZ31 Mg alloy underwent mechanical grinding using abrasive paper, and investigations were conducted into the microstructure development and corrosion behavior through open circuit potential analysis. A deformed layer, featuring nanocrystalline grains ranging in size from 40 to 250 nm, was produced using mechanical grinding. Within this deformed layer, the MgO layer and a 20-nm-thick Zn enrichment band were identified. The corrosion observations and the corrosion resistance mechanism resulting from open circuit potential results and electrochemical impedance spectroscopy have been discussed and proposed. The mechanically ground sample exhibited a significantly higher electronegative value of corrosion potential (− 1.595 V) compared to the unground AZ31 Mg sample (− 1.562 V). However, the open circuit potential value was maintained stable based on the continuous intensity of hydrogen gas released during the open circuit potential process. Following these results, the scratch/groove formed by mechanical grinding may serve as pathways for the propagation of corrosion, resembling filiform corrosion patterns. Based on the electrochemical test result, the mechanically ground sample displayed a corrosion resistance with impedance |Z|0.01 Hz values of 374 Ω cm2, slightly lower than that of the unground sample, suggesting an insignificant improvement in overall corrosion resistance for the mechanically ground sample. This successful characterization of the Mg alloy’s surface deformed layer and its correlation to corrosion behavior presents exciting possibilities for novel surface modifications in Mg alloys, potentially addressing challenges related to Mg reactivity.